Courseware perkara asas fardu 'ain (PAFA) untuk sekolah menengah - Helena, Mohd Nawawi; Siti Jamilah, Ahmad (University Malaysia Sarawak, UNIMAS., 2002)
Our country now is trying to create new generations who are educated and experienced in the Information Technology field. Starting from schools, they have to be exposed to this world. Teaching and learning methods have been developed for secondary school students, especially for PMR and SPM students.